Sustainability, Distributive Justice, and Law: A Philosophical Inquiry into the Compatibility of Environmental and Social Goals (UNWE Yearbook, 2024)
This essay aims at addressing the legal philosophy’s uptake on whether environmental sustainability can be integrated with distributive justice. After an analysis of the European legal framework, where the notion of sustainable development has been built, concepts such as the veil of ignorance, the capability approach, and human flourishing will be examined, arguing that sustainability and distributive justice are necessarily linked, as mutually reinforcing goals to human development. However, a transformational change is still necessary in the way we think about sustainability, to work towards a direction that should be holistic and inclusive of the needs of both people and the planet.